2015
DOI: 10.1002/jpln.201400080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autumn tillage and residue management on soil respiration in a long‐term field experiment in Sweden

Abstract: Several previous field studies in temperate regions have shown decreased soil respiration after conventional tillage compared with reduced or no-tillage treatments. Whether this decrease is due to differences in plant residue distribution or changes in soil structure following tillage remains an open question. This study investigated (1) the effects of residue management and incorporation depth on soil respiration and (2) biological activity in different post-tillage aggregates representing the actual size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…First, this model predicted that soil respiration increased by 16% as the temperature increased from 7.35°C to 13.35°C. This result is consistent with previous studies, which suggested that soil respiration has a significant positive correlation with temperature if soil water content is not a limiting factor ( Zhao et al, 2013; Kainiemi et al, 2015). Second, several publications suggested that the temperature sensitivity of soil respiration decreased with increasing temperature ( Zheng et al, 2009; Zhao et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…First, this model predicted that soil respiration increased by 16% as the temperature increased from 7.35°C to 13.35°C. This result is consistent with previous studies, which suggested that soil respiration has a significant positive correlation with temperature if soil water content is not a limiting factor ( Zhao et al, 2013; Kainiemi et al, 2015). Second, several publications suggested that the temperature sensitivity of soil respiration decreased with increasing temperature ( Zheng et al, 2009; Zhao et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…Our results show that although physical disruption of soils causes SOC losses, the C amounts released are so small that it would take many decades before they could be detected in field trials. This result is supported by previous field studies in Sweden ( Kainiemi et al, 2015), where it was found that the main factor driving soil respiration was management of plant residues and that physical disturbance of the soil structure had no significant effect.…”
Section: Resultssupporting
confidence: 87%
“…, Azooz et al., 1997). These reasons also explained higher respiration rates observed in the field when crop residues were left on the soil surface than when incorporated into the soil ( Kainiemi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in soil moisture and temperature and treatment-specific distribution of crop residues have been found to be highly important [e.g. [80][81][82][83]. According to a meta-analysis conducted by Virto et al [32] differences in SOC stocks between NT and inversion tillage were significantly and positively correlated with differences in crop yields.…”
Section: Direct and Indirect Effects Of Tillage On Soil Functions Andmentioning
confidence: 99%